Resistance to anti-PD-1/anti-PD-L1: galectin-3 inhibition with GB1211 reverses galectin-3-induced blockade of pembrolizumab and atezolizumab binding to PD-1/PD-L1 - Mabbitt, Joseph; Holyer, Ian D.; Roper, James A.; Nilsson, Ulf J.; Zetterberg, Fredrik R.; Vuong, Lynda; Mackinnon, Alison C.; Pedersen, Anders; Slack, Robert J. (Frontiers in Immunology, 2023)
Background: Galectin-3 (Gal-3) is a β-galactoside-binding lectin that is highly expressed within the tumor microenvironment of aggressive cancers and has been suggested to predict a poor response to immune checkpoint therapy with the anti-PD-1 monoclonal antibody pembrolizumab. We aimed to assess if the effect of Gal-3 was a result of direct interaction with the immune checkpoint receptor. Methods: The ability of Gal-3 to interact with the PD-1/PD-L1 complex in the absence and presence of blocking antibodies was assessed in in vitro biochemical and cellular assays as well as in an in vivo syngeneic mouse cancer model. Results: Gal-3 reduced the binding of the checkpoint inhibitors pembrolizumab (anti-PD-1) and atezolizumab (anti-PD-L1), by potentiating the interaction between the PD-1/PD-L1 complex. In the presence of a highly selective Gal-3 small molecule inhibitor (GB1211) the binding of the anti-PD-1/anti-PD-L1 therapeutics was restored to control levels. This was observed in both a surface plasmon resonance assay measuring protein-protein interactions and via flow cytometry. Combination therapy with GB1211 and an anti-PD-L1 blocking antibody reduced tumor growth in an in vivo syngeneic model and increased the percentage of tumor infiltrating T lymphocytes. Conclusion: Our study suggests that Gal-3 can potentiate the PD-1/PD-L1 immune axis and potentially contribute to the immunosuppressive signalling mechanisms within the tumor microenvironment. In addition, Gal-3 prevents atezolizumab and pembrolizumab target engagement with their respective immune checkpoint receptors. Reversal of this effect with the clinical candidate GB1211 offers a potential enhancing combination therapeutic with anti-PD-1 and -PD-L1 blocking antibodies.